Factors Affecting Purchase Intention of Over-the-top Platforms - Abbas, Syed Ali (2024)
While the convergence of industries is evident in many fields, online streaming is a phenomenon to research. Therefore, this study investigates factors affecting consumer purchase behavior for over-the-top (OTT) platform subscriptions. A quantitative study with a cross-section design is followed, whereas factor analysis for reliability and Partial Least Square Structural Equation Modelling has been applied for hypothesis testing. Results depict the positive impact of celebrity movies/ shows, the ratio of new releases, and the moderate positive effect of price on consumer purchase intention, whereas content quality acts as a positive moderator. The study with variables such as Celebrity Branding, Price, and New Releases in the context of OTT platforms in academic research is a rare practice. Practically, the results can benefit OTT platforms for enhancing user experience and understanding customer demand. It further opens horizons for practitioners to align academic research with the OTT streaming industry.   Sample regions encompass demographics where OTT is still uncommon to the majority. Also, OTT platforms may offer a wide array of factors that lack the existence of statistical variables to be incorporated into academic research.